Iban forest management and wildlife conservation along the Danau Sentarum periphery, West Kalimantan, Indonesia - Wadley, R.L. (2002)
Danau Sentarum National Park in West Kalimantan, Indonesia is bordered on three sides by Iban settlements and the forests they manage. The forest management system practiced by an Iban community on the northeastern periphery of the reserve is described here. Iban agroforestry is based on two principal components: swidden cultivation, which creates a field-secondary forest mosaic and various kinds of preserved and managed forest. Iban hunt within these forests, and the species and numbers of animals they encounter are analysed here with respect to their exploitation of the agroforests and fields. The merits and constraints of this management system are discussed. Based on the data analysed here, this system appears to promote some degree of biodiversity conservation and may serve as a partial buffer zone around the nearby wildlife reserve.